Method for inhibiting starch aging, method for acidolysis of cellulose and product
By mixing cellulose with acid and sonicating it with starch, the problem of starch aging in food is solved, and the effect of inhibiting starch aging is achieved without affecting the taste and appearance of the food.
Patent Information
- Application Number
- CN202311251960.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-26
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to effectively inhibit starch aging in food without affecting the taste and appearance of the food.
By mixing cellulose with acid, sonicating and mixing with organic solvent, a precipitate was obtained and starch was mixed to inhibit starch aging.
It achieves the effect of inhibiting starch aging without affecting the taste, color and texture of the food, extending the shelf life and edible experience of the food.
Smart Images

Figure BDA0004470544750000121 
Figure BDA0004470544750000131
Abstract
Description
Technical Field
[0001] The invention relates to the field of food, and in particular to a method for inhibiting starch aging and a method and product for acid-decomposing cellulose. Background Art
[0002] Starch aging refers to the phenomenon that the gelatinized starch gradually becomes opaque, coagulates and precipitates, and hardens, also known as retrogradation. In the food industry, starch aging can cause changes in the texture of food, such as deterioration of texture characteristics, decreased transparency, and rough taste, which can shorten the shelf life and eating experience of starch foods.
[0003] Cellulose, as an important water-insoluble dietary fiber, is the most widely distributed and abundant polysaccharide in nature, and has the potential to inhibit starch aging. However, cellulose is not soluble in water, and its introduction into food ingredients will have a negative impact on the food's sensory properties such as appearance, texture and taste. Therefore, it is necessary to develop a functional raw material that has a strong ability to inhibit starch aging without significantly affecting the taste and appearance of food. Summary of the invention
[0004] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a method for inhibiting starch aging and a method and product for acid hydrolyzing cellulose. The method can obtain a product with a strong ability to inhibit starch aging and which is more beneficial to the taste and appearance of food when applied in the food field.
[0005] In order to achieve the above object, the present invention provides a method for inhibiting starch aging, which comprises:
[0006] (1) mixing cellulose and an acid to obtain a mixture, subjecting the mixture to ultrasonic treatment, and mixing the material after the ultrasonic treatment with an organic solvent to obtain a precipitate;
[0007] The power of ultrasonic treatment is 7-12W / g mixture;
[0008] (2) mixing the precipitate obtained in step (1) with starch to inhibit starch aging.
[0009] The second aspect of the present invention provides a method for acid hydrolysis of cellulose, which is carried out according to step (1) of the method described in the first aspect.
[0010] The third aspect of the present invention provides an acid-decomposed cellulose product prepared by the method described in the second aspect.
[0011] By adopting the technical solution of the present invention, a product with strong ability to inhibit starch aging and good water solubility can be obtained, which is more beneficial to the taste and appearance of food when applied to the food field. In addition, by using the particularly preferred phosphoric acid and ultrasound of the present invention for combination, a product with strong ability to inhibit starch aging can be obtained with higher efficiency under milder and controllable conditions. DETAILED DESCRIPTION
[0012] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0013] In a first aspect, the present invention provides a method for inhibiting starch aging, the method comprising:
[0014] (1) mixing cellulose and an acid to obtain a mixture, subjecting the mixture to ultrasonic treatment, and mixing the material after the ultrasonic treatment with an organic solvent to obtain a precipitate;
[0015] The power of ultrasonic treatment is 7-12W / g mixture;
[0016] (2) mixing the precipitate obtained in step (1) with starch to inhibit starch aging.
[0017] The inventors of the present invention have found in their research that the precipitation product obtained according to step (1) of the above method has a significantly stronger ability to inhibit starch aging, and the precipitation contains water-soluble substances. When used to inhibit starch aging, it can not only obtain a better inhibitory effect, but also will not have a significant impact on the taste, color and texture of the food, and is more suitable for the actual production of starch food. In addition, the introduction of the above water-soluble substances into starch food also helps to improve the food texture, sensory properties and shelf life, and expands the application range of cellulose products in food processing.
[0018] According to the present invention, preferably, in the mixture, the mass ratio of acid to cellulose is 1:(20-25).
[0019] Preferably, in the mixture, the mass concentration of the acid is 80-85wt%.
[0020] Preferably, the acid is selected from at least one of sulfuric acid, phosphoric acid and acetic acid, more preferably phosphoric acid. The inventors of the present invention further found that the use of phosphoric acid can make the treatment of step (1) more controllable, and the obtained precipitation product has a stronger ability to inhibit starch aging, and the use of phosphoric acid will not introduce acid ions into the precipitation (phosphate can be less or almost absent in the prepared product), so that the safety of the prepared food can be further guaranteed.
[0021] According to the present invention, preferably, the power of ultrasonic treatment is 8-10 W / g mixture.
[0022] Preferably, the ultrasonic treatment time is 30-90 min, more preferably 55-65 min.
[0023] Preferably, the temperature of ultrasonic treatment is 30-60°C, more preferably 40-55°C.
[0024] Preferably, the frequency of the ultrasonic treatment is 30-120 kHz, more preferably 50-100 kHz.
[0025] Under the above conditions, the ability to inhibit starch aging can be further guaranteed.
[0026] During the ultrasonic treatment, the material may be stirred at a speed of 300-500 rpm.
[0027] According to the present invention, preferably, the organic solvent is selected from ethanol and / or methanol, preferably ethanol. When the above organic solvent is selected, not only can the reaction in the mixture be better terminated, but also the material generated by the reaction during the ultrasonic treatment can be better precipitated to be better separated from the mixture. The formed precipitate is generally white.
[0028] According to the present invention, preferably, the volume ratio of the mixture to the organic solvent is 1:(4-6).
[0029] According to the present invention, preferably, step (1) further comprises: separating a water-soluble portion from the precipitate, and using the water-soluble portion for mixing with starch in step (2). It is understandable that the precipitate contains a water-soluble portion and may also contain a water-insoluble portion. The inventors of the present invention further found that the water-soluble portion can better inhibit starch aging and can further ensure the taste and color of the starch product obtained by adding it to starch.
[0030] Before separating the water-soluble part from the precipitate, the precipitate may be dried (may be oven-dried) to remove the organic solvent contained therein, and the drying may be performed at 50-80° C. for 60-90 min.
[0031] According to the present invention, preferably, the method of separating the water-soluble part from the precipitate includes: mixing the precipitate and water, and performing solid-liquid separation to obtain a liquid phase, and drying the liquid phase to obtain a water-soluble part. Among them, the mass dosage of the precipitate and the water can be 1: (25-35), the method of solid-liquid separation can be centrifugation, the speed can be 800-1500rpm, and the time can be 5-10min. The drying method can be freeze-dried, which can be freeze-dried for 48-50h at a vacuum degree of -80 to -85°C and -0.0012 to -0.0014MPa. The solid phase obtained by solid-liquid separation is a water-insoluble part, which also has the effect of inhibiting starch aging. This part can also be freeze-dried (can be freeze-dried for 48-50h at a vacuum degree of -80 to -85°C and -0.0012 to -0.0014MPa) for standby use. The inventors of the present invention further discovered in their research that, compared with the water-insoluble part, the water-soluble part can have a better effect of inhibiting starch aging and can better ensure the taste and color appearance of the food obtained after application.
[0032] According to the present invention, preferably, in step (2), the mass ratio of precipitate to starch is 100:(0.2-3), more preferably 100:(0.3-2.1). Within the above range, the effect of inhibiting starch aging, as well as the taste and color appearance of the prepared food can be further ensured.
[0033] According to the present invention, preferably, the weight average molecular weight of the cellulose is 2000Da-2500Da (for example, it may be 2000Da, 2100Da, 2200Da, 2300Da, 2400Da, 2500Da, and a range formed by any two of the above values, and a value within the range).
[0034] According to the present invention, preferably, the method further comprises the step of obtaining cellulose from corn seed husks, which comprises: dehydrating the corn seed husks, defatting, removing starch, removing protein and hemicellulose, and removing lignin in sequence.
[0035] Obtaining cellulose from corn husks can make full use of corn husks, which are generally considered to have low value, and because corn husks are widely available, a higher cellulose yield can also be guaranteed.
[0036] Before dehydrating the soluble material, the corn husk can be cleaned, dried, and crushed to an average particle size of 0.1-0.3 mm (for example, it can be 0.1 mm, 0.15 mm, 0.18 mm, 0.2 mm, 0.25 mm, 0.3 mm, and a range formed by any two of the above values and a value within the range) to better carry out subsequent operations.
[0037] The present invention has no particular restrictions on the specific operations of dehydration, defatting, starch removal, protein and hemicellulose removal, and lignin removal, as long as the purpose of removing the above components can be achieved.
[0038] The method of dehydrating the soluble matter may include: mixing corn husk and water at a mass ratio of 1: (30-50), and stirring at 70-90° C. for 1-3 hours (the rotation speed may be 600-1000 rpm).
[0039] The degreasing method may include: mixing the corn husk after dehydration and the degreasing solvent at a mass ratio of 1: (20-25), and stirring at 20-30° C. for 3-5 hours (the rotation speed may be 400-600 rpm). The degreasing solvent may be a mixed solution of chloroform and methanol, wherein the volume ratio of chloroform to methanol may be (1.5-2.5):1.
[0040] The method of removing starch may include: mixing defatted corn husks with amylase, and reacting for 1-3 hours at 50-60°C and pH 6-7. The defatted corn husks may be dispersed in water, and the mass concentration of the defatted corn husks in the obtained dispersion may be 10-20wt%, and the pH may be adjusted to the above range, and then mixed with amylase, which may be a medium-temperature α-amylase (available from Megazyme). The amount of enzyme used may be 3.5×10 6 -4.0×10 6 U. The definition of the enzyme activity unit of mesophilic α-amylase is: the amount of enzyme required to liquefy 1 mg of soluble starch in 1 min at 55°C and pH 6.5.
[0041] After each step of dehydration, defatting and starch removal is completed, the material can be separated into solid and liquid (centrifugation can be performed at a speed of 600-1000 rpm for 10-15 min) to obtain a solid phase, which is then dried (at a temperature of 45-60° C. for 1-1.5 h). The dried corn husk is then processed later.
[0042] The method of removing protein and hemicellulose may include: mixing corn husk after starch removal with alkali, and reacting at 70-90° C. for 1-3 hours. The alkali may be used in the form of an aqueous solution of alkali, and in the mixed material, the mass concentration of the alkali may be 0.05-0.1wt%, and the mass concentration of corn husk after starch removal may be 20-25wt%. After the reaction, solid-liquid separation may be performed (centrifugation may be performed, the speed may be 400-600rpm, and the time may be 10-15min), and the obtained solid phase may be washed with pure water to a neutral pH value, and then the corn husk may be dried (the temperature may be 45-60° C., and the time may be 2-3h).
[0043] The method of removing lignin may include: mixing corn husks after removing protein and hemicellulose with sodium hypochlorite, reacting at 65-75°C for 1-3h, and washing the reacted corn husks to neutrality. In the mixed material, the mass concentration of sodium hypochlorite may be 2.5-3.5wt%, and the mass concentration of corn husks after removing protein and hemicellulose may be 20-30wt%. After the reaction, the material may be immediately cooled in an ice bath, and then solid-liquid separation may be performed (the speed may be 2500-3500rpm, and the time may be 15-25min) to obtain a solid phase, and the solid phase may be repeatedly washed with ice pure water until the pH is neutral. The material may then be freeze-dried (freeze-dried for 48-50h at -80 to -85°C and a vacuum degree of -0.0012 to -0.0014MPa). The freeze-dried material may be wet ball milled to make the material particle size more uniform, the ball volume ratio may be 1:(10-20), and the time may be 8-16h. After wet ball milling, freeze drying can be performed again (freeze drying can be performed at -80 to -85°C and a vacuum degree of -0.0012 to -0.0014 MPa for 48 to 50 hours) to obtain cellulose.
[0044] In a second aspect, the present invention provides a method for acid hydrolysis of cellulose, which is carried out according to step (1) of the method described in the first aspect.
[0045] As described above, by following step (1) of the method described in the first aspect, a product can be obtained that has a strong ability to inhibit starch aging and does not significantly affect the taste, color and texture of the food.
[0046] In a third aspect, the present invention provides an acid-decomposed cellulose product prepared by the method described in the second aspect.
[0047] The present invention will be described in detail below through cellulose preparation examples and examples.
[0048] In the following cellulose preparation example, before dehydrating the solubles, the corn husks were cleaned, dried, and crushed to an average particle size of 0.18 mm. After each step of dehydrating the solubles, defatting, and removing starch, the material was centrifuged at 800 rpm for 12 minutes, and the solid phase was dried at 50°C for 1 hour before being processed in the next step.
[0049] In the following cellulose preparation examples, the weight average molecular weight of cellulose was measured by GPC (gel chromatography, the equipment used was purchased from Shimadzu, Japan).
[0050] Cellulose Preparation Example 1
[0051] Dehydrated solution: corn husk and water were mixed in a mass ratio of 1:40 and stirred at 80°C for 2 h (rotation speed of 800 rpm).
[0052] Degreasing: The corn seed husk after dehydration was mixed with a degreasing solvent at a mass ratio of 1:20, and stirred at 25°C for 4 hours (speed of 500 rpm). The degreasing solvent was a mixture of chloroform and methanol at a volume ratio of 2:1.
[0053] Starch removal: defatted corn husks were dispersed in water (the mass concentration of defatted corn husks in the dispersion can be 12 wt%), the pH was adjusted to 6.5, and then medium-temperature α-amylase (purchased from Megazyme) was added. The enzyme dosage was 4.0×10 6 U; react at 55°C for 2h.
[0054] Removal of protein and hemicellulose: corn husks after starch removal and sodium hydroxide solution are mixed so that the mass concentration of corn husks after starch removal is 20wt% and the mass concentration of sodium hydroxide is 0.1wt% in the mixed solution; and react at 80°C for 2h. Then centrifuge (speed of 600rpm, time of 10min), and wash the obtained solid phase with pure water to a neutral pH value, and then dry the corn husk (temperature of 50°C, time of 2.5h).
[0055] Lignin removal: corn husks after protein and hemicellulose removal are mixed with sodium hypochlorite aqueous solution and reacted at 65°C for 3h. The mass concentration of sodium hypochlorite in the mixture is 3wt%, and the mass concentration of corn husks after protein and hemicellulose removal is 20wt%. After the reaction, the material is immediately cooled in an ice bath, and then solid-liquid separation is performed (speed is 3500rpm, time is 15min) to obtain a solid phase, which is repeatedly washed with ice pure water until the pH is neutral. Then the material is freeze-dried at -80°C and -0.0014MPa vacuum for 48h. And the freeze-dried material is wet ball milled, with a ball volume ratio of 1:15, and the time can be 12h. Then the wet ball milled material is freeze-dried (-85°C, vacuum degree of -0.0014MPa for 48h) to obtain cellulose.
[0056] The weight average molecular weight of cellulose is 2100 Da.
[0057] Cellulose Preparation Example 2
[0058] Dehydrated solution: corn husk and water were mixed in a mass ratio of 1:50 and stirred at 90°C for 3 h (rotation speed was 1000 rpm).
[0059] Degreasing: The corn husk after dehydration was mixed with the degreasing solvent at a mass ratio of 1:25, and stirred at 28°C for 3 hours (speed of 600 rpm). The degreasing solvent was a mixture of chloroform and methanol at a volume ratio of 2.5:1.
[0060] Starch removal: defatted corn husks were dispersed in water (the mass concentration of defatted corn husks in the dispersion may be 16 wt%), the pH was adjusted to 6.8, and then medium-temperature α-amylase (purchased from Megazyme) was added, wherein the amount of enzyme used was 3.5×10 6 U; and react at 60°C for 1 h.
[0061] Removal of protein and hemicellulose: corn husks after starch removal and sodium hydroxide solution are mixed so that the mass concentration of corn husks after starch removal is 25wt% and the mass concentration of sodium hydroxide is 0.08wt% in the mixed solution; and the mixture is reacted at 90°C for 1.5h. Then centrifugation is performed (speed is 500rpm, time is 12min), and the obtained solid phase is washed with pure water to a neutral pH value, and then the corn husks are dried (temperature is 60°C, time is 3h).
[0062] Lignin removal: corn husks after protein and hemicellulose removal are mixed with sodium hypochlorite aqueous solution and reacted at 75°C for 1 hour. The mass concentration of sodium hypochlorite in the mixture is 3wt%, and the mass concentration of corn husks after protein and hemicellulose removal is 23wt%. After the reaction, the material is immediately cooled in an ice bath, and then solid-liquid separation is performed (speed is 2500rpm, time is 25min) to obtain a solid phase, which is repeatedly washed with ice pure water until the pH is neutral. Then the material is freeze-dried at -85°C and -0.0012MPa vacuum for 50 hours. And the freeze-dried material is wet ball milled, with a ball volume ratio of 1:20, and the time can be 16 hours. Then the wet ball milled material is freeze-dried (conditions -80°C, vacuum degree of -0.0012MPa for 50 hours) to obtain cellulose.
[0063] The weight average molecular weight of cellulose is 2500 Da.
[0064] Example 1
[0065] The cellulose obtained in Cellulose Preparation Example 1 was mixed with a phosphoric acid aqueous solution so that the mass ratio of the acid to the cellulose in the mixture was 1:20 and the mass concentration of the phosphoric acid in the mixture was 85 wt %. The mixture was stirred until the cellulose was completely soaked.
[0066] The mixture was subjected to ultrasonic treatment at a power of 10 W / g mixture, a frequency of 50 kHz, a time of 60 min, a temperature of 45° C., and stirring at a rotation speed of 500 rpm.
[0067] After the ultrasonic treatment, the reaction mixture was mixed with ethanol, the volume of which was 5 times the volume of the mixture. After mixing, a precipitate was formed. The precipitate was then dried at 50° C. for 90 min.
[0068] The dried precipitate and water were mixed at a mass ratio of 1:25, and then centrifuged at 1000 rpm for 10 min to obtain a liquid phase and a solid phase, respectively. The liquid phase was freeze-dried at -85°C and a vacuum degree of -0.0014 MPa for 48 h.
[0069] Example 2
[0070] The cellulose obtained in Preparation Example 1 was mixed with a phosphoric acid aqueous solution so that the mass ratio of the acid to the cellulose in the mixture was 1:22 and the mass concentration of the phosphoric acid in the mixture was 80 wt %. The mixture was stirred until the cellulose was completely soaked.
[0071] The mixture was subjected to ultrasonic treatment at a power of 9 W / g mixture, a frequency of 60 kHz, a time of 55 min, a temperature of 50° C., and stirring at a rotation speed of 400 rpm.
[0072] After the ultrasonic treatment, the reaction mixture was mixed with ethanol, the volume of which was 4 times the volume of the mixture. After mixing, a precipitate was formed. The precipitate was then dried at 60° C. for 80 min.
[0073] The dried precipitate and water were mixed at a mass ratio of 1:30, and then centrifuged at 1200 rpm for 8 minutes to obtain a liquid phase and a solid phase, respectively. The liquid phase was freeze-dried at -80°C and a vacuum degree of -0.0013 MPa for 50 hours.
[0074] Example 3
[0075] The cellulose obtained in Preparation Example 1 was mixed with a phosphoric acid aqueous solution so that the mass ratio of the acid to the cellulose in the mixture was 1:25 and the mass concentration of the phosphoric acid in the mixture was 82 wt %. The mixture was stirred until the cellulose was completely soaked.
[0076] The mixture was subjected to ultrasonic treatment with an ultrasonic power of 8 W / g mixture, a frequency of 90 kHz, a time of 65 min, a temperature of 55° C., and stirring during the treatment at a rotation speed of 300 rpm.
[0077] After the ultrasonic treatment, the reaction mixture was mixed with ethanol, the volume of which was 6 times the volume of the mixture. After mixing, a precipitate was formed. The precipitate was then dried at 80°C for 60 minutes.
[0078] The dried precipitate and water were mixed at a mass ratio of 1:35, and then centrifuged at 1500 rpm for 5 minutes to obtain a liquid phase and a solid phase, respectively. The liquid phase was freeze-dried at -82°C and a vacuum degree of -0.0012 MPa for 49 hours.
[0079] Example 4
[0080] The method of Example 1 was followed, except that cellulose was replaced by cellulose obtained in Cellulose Preparation Example 2. The results are shown in Table 1.
[0081] Example 5
[0082] The method of Example 1 is followed, except that the frequency of the ultrasound is 30 kHz.
[0083] Example 6
[0084] The method of Example 1 was followed, except that the ultrasonication time was 80 min.
[0085] Example 7
[0086] The method of Example 1 is followed, except that the mass concentration of acid in the mixture of cellulose and phosphoric acid aqueous solution is 55 wt %.
[0087] Example 8
[0088] The method of Example 1 was followed, except that phosphoric acid was substituted for acetic acid.
[0089] Comparative Example 1
[0090] The method of Example 1 is followed, except that ultrasound is turned off.
[0091] Comparative Example 2
[0092] The method of Example 1 was followed, except that the power of the ultrasonic treatment was 4 W / g mixture.
[0093] The inventors of the present invention have found that, compared with Example 8, the use of Example 1 can make the operation process more controllable, can also avoid the introduction of acid ions into the prepared product, and can achieve a higher yield when preparing the product.
[0094] Test Example 1
[0095] A key manifestation of starch aging after gelatinization is the increase in the hardness of the starch gel. Therefore, the product's ability to inhibit starch aging can be characterized by measuring the hardness.
[0096] Take the products prepared in the above examples and comparative examples (hereinafter referred to as inhibitors) and carry out the following steps respectively:
[0097] The inhibitor and starch were mixed to obtain samples A and D with a mass ratio of starch to inhibitor of 100:0.3, samples B and E with a ratio of 100:1.2, and samples C and F with a ratio of 100:2.1, and each sample was mixed with water at a mass ratio of 1:25 to form a dispersion. The dispersion corresponding to sample A, sample B and sample C was heated at 95°C for 20 minutes to form gelatinized starch. The dispersion corresponding to sample D, sample E and sample F was heated at 140°C for 20 minutes to form gelatinized starch. After gelatinization, it was allowed to stand for 0.5 hours, and then the hardness of the starch gel was measured by a texture analyzer (TMS-Pro).
[0098] In addition, control experiment 1 was conducted, namely, starch and water were mixed at a mass ratio of 1:25 to form a dispersion, and the dispersion was heated at 95°C and 140°C for 20 minutes to form gelatinized starch. After standing for 0.5 hours, the hardness was measured in the same manner as above.
[0099] In control experiment 2, microcrystalline cellulose (purchased from Sigma, item number 11363-250G 9004-34-6) was mixed with starch to obtain samples A and D with a mass ratio of starch to microcrystalline cellulose of 100:0.3, samples B and E with a ratio of 100:1.2, and samples C and F with a ratio of 100:2.1, respectively. Each sample was mixed with water at a mass ratio of 1:25 to form a dispersion, and the dispersion corresponding to sample A, sample B and sample C was heated at 95°C for 20 minutes, and the dispersion corresponding to sample D, sample E and sample F was heated at 140°C for 20 minutes to form gelatinized starch. After standing for 0.5 hours, the hardness was measured in the same manner as above.
[0100] In control experiment 3, the cellulose prepared in cellulose preparation example 1 was mixed with starch to obtain samples A and D with a starch to cellulose mass ratio of 100:0.3, samples B and E with a ratio of 100:1.2, and samples C and F with a ratio of 100:2.1, respectively. Each sample was mixed with water at a mass ratio of 1:25 to form a dispersion, and the dispersion corresponding to sample A, sample B and sample C was heated at 95°C for 20 minutes, and the dispersion corresponding to sample D, sample E and sample F was heated at 140°C for 20 minutes to form gelatinized starch. After standing for 0.5 hours, the hardness was measured in the same manner as above.
[0101] The results are shown in Table 1.
[0102] Table 1
[0103]
[0104]
[0105] It is understandable that in general households or restaurants, the cooking temperature is 95-100°C, and in the production of food industry, such as the production of pre-prepared dishes, the products are generally sterilized at 130-140°C. The above experiments can show that the inhibitor provided by the present invention can exert a good inhibitory effect at a temperature of 95-140°C, so the method provided by the present invention is applicable to daily life or food industry.
[0106] It can also be seen from the results in Table 1 that the inhibitors prepared by the embodiments of the present invention, especially the inhibitors of Examples 1-4, can have a good effect of inhibiting starch retrogradation at a relatively small addition amount. The inhibitor provided by the present invention has a good white color when in powder form and has good water solubility, so when used in food production, it will not have a significant effect on the taste, color and texture of the food.
[0107] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for inhibiting starch aging, characterized in that: The method includes: (1) mixing cellulose and an acid to obtain a mixture, subjecting the mixture to ultrasonic treatment, and mixing the material after the ultrasonic treatment with an organic solvent to obtain a precipitate; The power of ultrasonic treatment is 7-12W / g mixture; (2) mixing the precipitate obtained in step (1) with starch to inhibit starch aging.
2. The method according to claim 1, wherein: In step (1), the mass ratio of acid to cellulose in the mixture is 1:(20-25); and / or, in the mixture, the mass concentration of the acid is 80-85wt%; And / or, the acid is selected from at least one of sulfuric acid, phosphoric acid and acetic acid, more preferably phosphoric acid.
3. The method according to claim 1, wherein: The power of ultrasonic treatment was 8-10 W / g mixture; And / or, the ultrasonic treatment time is 30-90 min, preferably 55-65 min; and / or, the temperature of ultrasonic treatment is 30-60° C., preferably 40-55° C.; And / or, the frequency of the ultrasonic treatment is 30-120 kHz, preferably 50-100 kHz.
4. The method according to claim 1 or 2, wherein: The organic solvent is selected from ethanol and / or methanol, preferably ethanol; And / or, the volume ratio of the mixture to the organic solvent is 1:(4-6).
5. The method according to claim 1 or 3, wherein: Step (1) further comprises: separating a water-soluble portion from the precipitate, and using the water-soluble portion for mixing with starch in step (2); Preferably, the method of separating the water-soluble portion from the precipitate includes: mixing the precipitate and water, performing solid-liquid separation to obtain a liquid phase, and drying the liquid phase to obtain the water-soluble portion.
6. The method according to claim 1, wherein: In step (2), the mass ratio of precipitate to starch is 100:(0.2-3), preferably 100:(0.3-2.1).
7. The method according to claim 1 or 6, wherein: The weight average molecular weight of the cellulose is 2000Da-2500Da; And / or, the method further comprises the step of obtaining cellulose from corn seed husks, the step comprising: sequentially dehydrating the corn seed husks, defatting, removing starch, removing protein and hemicellulose, and removing lignin.
8. The method according to claim 7, wherein: The method of dehydrating the soluble matter includes: mixing corn husk and water at a mass ratio of 1: (30-50), and stirring at 70-90° C. for 1-3 hours; And / or, the degreasing method includes: mixing the corn husk after dehydration and the degreasing solvent at a mass ratio of 1: (20-25), and stirring at 20-30° C. for 3-5 hours; And / or, the starch removal method includes: mixing defatted corn husks with amylase, and reacting at 50-60° C. and pH 6-7 for 1-3 hours; And / or, the method of removing protein and hemicellulose includes: mixing corn husk after starch removal with alkali, and reacting at 70-90° C. for 1-3 hours; And / or, the method of removing lignin includes: mixing corn husks after removing protein and hemicellulose with sodium hypochlorite, reacting at 65-75° C. for 1-3 hours, and washing the reacted corn husks to neutrality.
9. A method for acid hydrolyzing cellulose, characterized in that: The method is carried out according to step (1) of the method according to any one of claims 1 to 8.
10. The acid-decomposed cellulose product prepared by the method of claim 9.